Mediastinal Germ Cell Tumors in Pediatric Patients: A Report From the Italian Association of Pediatric Hematology and Oncology. Issue 5 (14th January 2016) - De Pasquale, Maria Debora; Crocoli, Alessandro; Conte, Massimo; Indolfi, Paolo; D'Angelo, Paolo; Boldrini, Renata; Terenziani, Monica; Inserra, Alessandro
Abstract : Background: Primary mediastinal germ cell tumors (GCTs) are rare in children and still represent a challenge for both adult and pediatric oncologists because of their worse outcome compared to their gonadal counterpart. Procedure: Prospectively collected data concerning patients enrolled in the Italian Association of Pediatric Haematology and Oncology study on malignant GCTs (AIEOP TCGM 2004) protocol for the treatment of GCTs were analyzed. Patients with malignant mediastinal primary GCTs were included in this study. Data regarding patients with newly diagnosed mediastinal teratoma were also collected. Results: From 2005 to 2013, 20 children diagnosed with mediastinal GCTs were registered in AIEOP TCGM 2004 protocol. With a median follow‐up of 89 months (range 35–123), the overall survival (OS) and event free survival (EFS) rates were 100% for teratoma and 90% for malignant GCTs. Conclusions: We confirm the favorable outcome of children affected by mediastinal teratoma and malignant GCTs. For malignant tumors, further studies on the clinical characteristics and genetic signatures on tumor samples might be necessary to better understand differences observed in high‐risk patients and to assist the development of more effective treatment for this subgroup.